Pastoral Care, Diakonia, dan Dukungan Psikososial Awal Orang Dengan Gangguan Jiwa sebagai Praksis Missio Dei di Yayasan Talitakum Cahaya Batam – Rumah Singgah Kasih-Kasihan, Tanjung Piayu Batam - Jabes Pasaribu; Selvyen Sophia; Timotius Mangiring Tua Togatorop; Renson Siahaan; Aprilius Nahak; Pestaria Sitorus; Michael Frisky Purba; Dewi Lidya Sidabutar; Linda Dewi Terserani Lase; Hana Priskila Saogo (Akoloutheo: Jurnal Pengabdian Kepada Masyarakat, 2026)
The marginalization of People with Mental Health Disorders (Orang Dengan Gangguan Jiwa, ODGJ) in Indonesia unfolds within a paradoxical space, in which faith communities theologically called to be sites of restoration frequently reproduce stigma through spiritual and moral attributions of psychic suffering. The realities of pasung (shackling), structural poverty, and the limited provision of mental health services deepen such exclusion, while theological education in Indonesia has not yet fully addressed the disjunction between academic space and vulnerable bodies. This article offers a reflection on a community service program conducted by the Undergraduate Theology Program of STT Real Batam at Rumah Singgah Talitakum Cahaya Batam, with residents undergoing rehabilitation for mental health disorders as its target participants. The program was carried out through a participatory approach integrating pastoral accompaniment, spiritual education grounded in John 14:27, communal prayer, distribution of basic food supplies, and relational interaction. The impact analysis is constructed upon the integration of four theoretical frameworks, namely spiritual well-being, pastoral care, diakonia as reciprocal service, and missio Dei as participation in the work of God. The findings indicate that pastoral presence contributes to the existential well-being of participants, strengthens the social capital of the shelter, and forms ethical sensitivity and ministerial competence among theology students. Furthermore, the program demonstrates that ministry to ODGJ can be read as a locus theologicus that contests the charitable paradigm and shifts ministry toward diaconal resonance. The contribution of this article lies in proposing a model of contextual theological engagement that integrates psychosocial rehabilitation, student formation, and the church's mission for marginal communities.